2018
DOI: 10.1186/s12864-018-5047-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analyses of the pectate lyase (PEL) gene family in cotton (Gossypium hirsutum L.)

Abstract: BackgroundPectin is a major component and structural polysaccharide of the primary cell walls and middle lamella of higher plants. Pectate lyase (PEL, EC 4.2.2.2), a cell wall modification enzyme, degrades de-esterified pectin for cell wall loosening, remodeling and rearrangement. Nevertheless, there have been few studies on PEL genes and no comprehensive analysis of the PEL gene family in cotton.ResultsWe identified 53, 42 and 83 putative PEL genes in Gossypium raimondii (D5), Gossypium arboreum (A2), and Gos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…qFL‐A03‐1 , detected in four environments, overlapping with qFS‐A03‐1 , qFU‐A03‐1 and qBW‐A03‐1 in Cluster‐A03‐1, was positioned at 75.3–84.5 Mb on A03, where a pectate lyase gene ( PEL6 , Gh_A03G1147 ), responsible for degrading pectin (Sun et al ., ), was located. The RNA‐seq data and RT‐qPCR results indicated that Gh_A03G1147 was relatively highly expressed during the earlier stages (0 and 5 DPA) of fibre development and had significantly higher expression in LMY22 than in LY343.…”
Section: Resultsmentioning
confidence: 99%
“…qFL‐A03‐1 , detected in four environments, overlapping with qFS‐A03‐1 , qFU‐A03‐1 and qBW‐A03‐1 in Cluster‐A03‐1, was positioned at 75.3–84.5 Mb on A03, where a pectate lyase gene ( PEL6 , Gh_A03G1147 ), responsible for degrading pectin (Sun et al ., ), was located. The RNA‐seq data and RT‐qPCR results indicated that Gh_A03G1147 was relatively highly expressed during the earlier stages (0 and 5 DPA) of fibre development and had significantly higher expression in LMY22 than in LY343.…”
Section: Resultsmentioning
confidence: 99%
“…The RD22-like, PG1β-like and BURP VIII subfamilies were composed of BURP members from monocots and dicots, indicating that these genes might have originated before the divergence of monocots and dicots [10, 12]. However, the members of other subfamilies were only from investigated monocots (BURP VI and BURP VII) or dicots (USP-like, BNM2-like and BURP V subfamilies), indicating that these genes might evolve separately and perform different functions between monocots and dicots [9, 13, 45]. Some results were different from previous studies due to the different methods and species used in the phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sequence alignment was performed using identified BURP proteins with ClustalX 2.0. The locations of conserved BURP domains and potential signal peptides of these proteins were determined using SMART database and SignalP 4.0 server (http://www.cbs.dtu.dk/services/SignalP/), respectively [45, 62].…”
Section: Methodsmentioning
confidence: 99%
“…The multiple sequences of GhWAKs and five AtWAKs (AT1G21210.1, AT1G21230.1, AT1G21240.1, AT1G21250.1 and AT1G21270.1) were aligned using ClustalX 2.0 [ 63 ], and an unrooted phylogenetic tree was generated using the NJ method in MEGA 7.0 [ 64 ].…”
Section: Methodsmentioning
confidence: 99%